On the solvability of boundary-value problems with continuous and generalized gluing conditions for the equation of mixed type with loaded term - Baltaeva, U. I. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the unique solvability of the boundary-value problems with normal derivatives and continuous and generalized gluing conditions for a loaded equation of the third order.